The Cross-Cultural Collaboration in Islamic Education Management - Amri, Zainu; Saputra, Dedi; Prayogi, Endar Evta Yuda (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The In the era of globalization, cross-cultural collaboration has become increasingly important in educational management, including within Islamic educational institutions operating in multicultural societies. This study aims to explore the application of cross-cultural collaboration in Islamic educational management and its impact on students' character development and multicultural understanding. Using a descriptive qualitative approach, data were collected through interviews, observations, and literature reviews to identify cross-cultural collaboration patterns within Islamic educational environments. The findings reveal that cross-cultural collaboration in Islamic educational institutions not only enhances students' understanding of cultural diversity but also strengthens social relationships among students and educators. However, challenges such as differences in values, language, and communication styles hinder the collaboration process. The implications of this study suggest that cross-cultural collaboration in Islamic educational management requires support from inclusive educational policies and the development of a culturally responsive curriculum. This study contributes to improving collaborative practices in Islamic educational institutions as a means of fostering a more tolerant and open-minded generation.